(3GdLed hGdYbhOs - (3eMeO Hf GdMSf Hf Ydj GdWhSj , CHh LYaQ,J (B460 (3g` s ((3eMeO Hf GdTjN WGgQ GdSeGhi s)
(3ChdgG (B:s
(3CeG HYO aCfG eLjH Edi eG SCd GdTjN GdaGVd CWGd Gddg HbGAg s
(3BNQgG (B:s
(3agPg Led bO dNUfGgG hYbOfGgG ai cd cJGH Ydi ZGjI LgOfG hWGbJfG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B84 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B202s
Keywords: (3abg GdePGgH GdCNQis